(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The most frequently used organic compounds are Schiff bases. They have been demonstrated to have a broad variety of biological activities. Using a thermal method, the synthesis of a series of imine derivatives 4a-f from Amino triazole thiol (3) as starting material with six different aldehydes. Target compounds’ full characterization was achieved using 1H and 13C- NMR, mass spectra, and FT-IR. In the 1H-NMR spectra of compounds (4a-f), an isotope with a proton signal for the CH of the azomethine group that ranged from 8 to 10.30 ppm was observed. Due to labile hydrogen bonds with nitrogen and sulfur, compound 3 exists in two tautomeric forms. Synthesis compounds’ antibacterial activity was investigated against the bacteria Klebsiella, E. coli and, S. aureus.